Comparison of Severe Viral Pneumonia Caused by SARS-CoV-2 and Other Respiratory Viruses Among Malaysian Children During the COVID-19 Pandemic - Ng, David Chun-Ern; Tan, Kah Kee; TING, Grace Sieng Sing; Ling, Chin; Fadzilah, Nur Fadzreena Binti; TAN, Shir Fong; Subramaniam, Thayasheri; Zailanalhuddin, Nur Emylia Binti; LIM, Hui Yi; Baharuddin, Suhaila Binti; LEE, Yee Lean; Mohamad Nor, Airena; et al. (Frontiers in Pediatrics, 2022)
Objectives: We described the etiology of severe pneumonia in children during the height of the COVID-19 pandemic in Malaysia and compared the clinical features of severe SARS-CoV-2 to other respiratory viruses. Methods: This retrospective study included all children aged 12 years and below hospitalized with severe pneumonia in Negeri Sembilan, Malaysia, between 1 April 2021 and 31 October 2021. We extracted demographic and clinical data and used logistic regression to examine risk factors associated with severe SARS-CoV-2 or other viral pneumonia. Results: A total of 111 children were included. The median age was 15 months. Human rhinovirus/enterovirus, SARS-CoV-2 and respiratory syncytial virus were the most common etiology of severe pneumonia. Codetection of >1 viral pathogen was present in 14 (12.6%) patients. Children with severe COVID-19 presented early in the course of illness and had lower rates of pediatric intensive care admission. The presence of sick contact with an adult was a predictor for SARS-CoV-2, whereas adventitious breath sounds were predictive of other respiratory viruses. Conclusions: The etiology of severe pneumonia in children evolved with the epidemic curve of COVID-19 and school closures. Children with severe pneumonia due to SARS-CoV-2 experienced a milder clinical course when compared to other respiratory viruses.